Mind the gap – unequal from the start: evidence from the early years of the Growing Up in New Zealand longitudinal study. Issue 3 (27th May 2022) - Morton, Susan M. B.; Napier, Carin; Morar, Manisha; Waldie, Karen; Peterson, Elizabeth; Atatoa Carr, Polly; Meissel, Kane; Paine, Sarah-Jane; Grant, Cameron C.; Bullen, Pat; Fenaughty, John; Bird, Amy; et al.
ABSTRACT: Growing Up in New Zealand is this country's largest contemporary longitudinal study of child development. The study has been designed to provide insight into the lives of children and young people growing up in the context of twenty-first century New Zealand. The Growing Up in New Zealand cohort recruited 6853 children representative of the current ethnic and socioeconomic diversity of births in Aotearoa, New Zealand in 2009 and 2010. The developmental wellbeing of the children has been tracked in detail over their first thousand days of life and every two to three years since. While the majority of the cohort are growing up healthy and happy, a significant proportion of children are growing up in families who have been persistently burdened with multiple stressors associated with economic, material and social hardship. This has created a disproportionate burden of poorer overall wellbeing outcomes and limited life course opportunities for these children from an early age. This paper will explore some of the evidence collected from the diverse cohort of New Zealand children and their families and whānau from before birth to middle childhood, highlighting the key findings and the utility of the evidence to improve wellbeing.